2010
DOI: 10.1007/s11424-010-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic limits and stabilization for the 1D nonlinear Mindlin-Timoshenko system

Abstract: This paper shows how the so called von Kármán model can be obtained as a singular limit of a modified Mindlin-Timoshenko system when the modulus of elasticity in shear k tends to infinity, provided a regularizing term through a fourth order dispersive operator is added. Introducing damping mechanisms, the authors also show that the energy of solutions for this modified Mindlin-Timoshenko system decays exponentially, uniformly with respect to the parameter k. As k → ∞, the authors obtain the damped von Kármán m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Finally in order to get the term −  Ω ξ 2 t dx we define the functional (33) and prove the following lemma.…”
Section: Now Using the Assumption (27) Lemma 2 And The Relationmentioning
confidence: 99%
“…Finally in order to get the term −  Ω ξ 2 t dx we define the functional (33) and prove the following lemma.…”
Section: Now Using the Assumption (27) Lemma 2 And The Relationmentioning
confidence: 99%
“…This last observation may have led some authors to use two feedback controls to exponentially stabilize the Timoshenko system independently of (1); e.g. [3,6,11]. The present note fits in the latter framework, but the damping scheme involves the same feedback control in both equations unlike the cited works where two independent controls are employed.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 83%
“…In [4], Araruna et al have showed how the so called von Kármán model (6) can be obtained as a singular limit of a modified Mindlin-Timoshenko system (4) when the modulus of elasticity in shear k tends to infinity, provided a regularizing term through a fourth order dispersive operator is added. Introducing damping mechanisms, the authors also show that the energy of solutions for this modified Mindlin-Timoshenko system decays exponentially, uniformly with respect to the parameter k. As k −→ ∞, the authors obtain the damped von Kármán model with associated energy exponentially decaying to zero as well.…”
mentioning
confidence: 99%
“…Uniqueness can be proved by the straightforward methods and Gronwall's inequality. 4. General decay.…”
mentioning
confidence: 99%